Perceived Quality and Brand Loyalty Mediated by Brand Trust among Garnier Bandung - Rosi Aura Maulida; Henny Utarsih (Pustaka Bangsa Indonesia, 2026)
This study examines the relationship between perceived quality and brand loyalty with brand trust as a mediating variable in the context of Garnier facial moisturizer consumers in Bandung, Indonesia. Background Problems: Increasing competition from local skincare brands has weakened consumer loyalty toward global brands, including Garnier. Novelty: This study specifically focuses on Garnier facial moisturizers and empirically tests the mediating role of brand trust, which has received limited attention in prior studies. Research Methods: A quantitative approach was employed using survey data collected from 120 Garnier users and analyzed through Partial Least Squares–Structural Equation Modeling (PLS-SEM). Findings/Results: The results show that perceived quality has a significant positive effect on brand trust and brand loyalty, while brand trust significantly influences brand loyalty and mediates the relationship between perceived quality and brand loyalty. Conclusion: Improving perceived quality strengthens brand trust, which in turn enhances consumer loyalty toward Garnier facial moisturizers.